Natural Resource Production and the Risk of Conflict Recurrence. (2nd January 2018) - Roy, Vita
ABSTRACT: Do different types of natural resources have varying impacts on the risk of conflict recurrence? Using a classification of high-value natural resources according to their lootability and obstructability, this article develops a framework bridging research on natural resources and conflict recurrence. I find evidence for the destabilizing character of easily lootable resources that is coherent across different conflict data. Non-lootable resources show little robust effects at first sight; but when introducing a measure of obstructability, the analysis uncovers varying effects of obstructable and non-obstructable resources that interact with the mode of conflict termination. Overall, the results underline the importance of attending to the lootability and obstructability dimension of natural resources when researching post-conflict risks in resource endowed states.